Exchange intervention and determination of the type of change in the short term: the Peruvian evidence - Shiva Ramayoni, Marco (Universidad del Pacífico, 2003)
This article explores the main characteristics and stylized facts of the exchange rate behavior in Peru and the Central Bank interventions in the foreign exchange market. In this sense, our aim is to model the monetary authority’s decision of participation in the market, by selling or buying dollars. We also try to determine the relative importance of the set of variables considered as potentially relevant in the price determination process of the dollar. Finally we try to assess the implications of these findings over the financial system performance. Weuse daily data and a new methodology, which allows us to reveal and explore in a better way the short run behavior of the exchange rate in Peru.